Noise and Vibration in Friction Systems - Sergienko, Vladimir P (Springer, 2016)
The book analyzes the basic problems of oscillation processes and theoretical aspects of noise and vibration in friction systems. It presents generalized information available in literature data and results of the authors in vibroacoustics of friction joints, including car brakes and transmissions. The authors consider the main approaches to abatement of noise and vibration in non-stationary friction processes. Special attention is paid to materials science aspects, in particular to advanced composite materials used to improve the vibroacoustic characteristics of tribopairs The book is intended for researchers and technicians, students and post-graduates specializing in mechanical engineering, maintenance of machines and transport means, production certification, problems of friction and vibroacoustics.